Reproducible generation of human retinal ganglion cells from banked retinal progenitor cells: analysis of target recognition and IGF-1-mediated axon regeneration - Subramani, Murali; Van Hook, Matthew J.; Ahmad, Iqbal (Frontiers in Cell and Developmental Biology, 2023)
The selective degeneration of retinal ganglion cells (RGCs) is a common feature in glaucoma, a complex group of diseases, leading to irreversible vision loss. Stem cell-based glaucoma disease modeling, cell replacement, and axon regeneration are viable approaches to understand mechanisms underlying glaucomatous degeneration for neuroprotection, ex vivo stem cell therapy, and therapeutic regeneration. These approaches require direct and facile generation of human RGCs (hRGCs) from pluripotent stem cells. Here, we demonstrate a method for rapid generation of hRGCs from banked human pluripotent stem cell-derived retinal progenitor cells (hRPCs) by recapitulating the developmental mechanism. The resulting hRGCs are stable, functional, and transplantable and have the potential for target recognition, demonstrating their suitability for both ex vivo stem cell approaches to glaucomatous degeneration and disease modeling. Additionally, we demonstrate that hRGCs derived from banked hRPCs are capable of regenerating their axons through an evolutionarily conserved mechanism involving insulin-like growth factor 1 and the mTOR axis, demonstrating their potential to identify and characterize the underlying mechanism(s) that can be targeted for therapeutic regeneration.